`e^(-2x) - 2xe^(-2x) = 0` Solve the equation algebraically. Round your result to three decimal places. Verify your answer using a graphing utility.

kspcr111 | Student

e^(-2x) - 2xe^(-2x) = 0

Taking the term e^(-2x) as common we get,

=>   e^(-2x)[1-2x]=0

=>   ((1-2x)/(e^(2x))) =0

=> (1-2x) = 0 * (e^(2x))

=> 1-2x =0

=> x = 1/2 = 0.500

the below graphs are

1) e^(-2x) - 2xe^(-2x) = 0

2) y= e^(-2x) - 2xe^(-2x)

Images:
This image has been Flagged as inappropriate Click to unflag
Image (1 of 2)
This image has been Flagged as inappropriate Click to unflag
Image (2 of 2)